Bandwidth limitations matching of electrically-small whip antennas with non-foster network - A. A. Golovkov; E. I. Mozhaeva (Известия высших учебных заведений России: Радиоэлектроника, 2016)
Calculated reception restriction small whip antenna bandwidth electrically small restrictions Bode-Fano for chains with foster elements. The relationship between the minimum value of the reflection coefficient of the antenna and the operating frequency band as possible.